CONCEPTUAL FOUNDATIONS OF HEALTH-IMPROVING PHYSICAL ACTIVITY IN MODERN SOCIETY - V.Sh. Rakhimov, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  article  examines  the  conceptual  foundations  and  methodological approaches to organizing health-improving physical activity within modern society. The study focuses on developing a comprehensive health promotion concept based on systematic physical activity, individualized approaches, and the integration of modern monitoring technologies. The results of the pedagogical experiment demonstrate that regular  and  structured  physical  activity  significantly  improves  physical  fitness indicators,  including  strength,  endurance,  flexibility,  and  functional  condition (p